Sports vision training: A review of the state-of-the-art in digital training techniques. Issue 1 (1st January 2018) - Appelbaum, L. Gregory; Erickson, Graham
ABSTRACT: Athletes need excellent vision to perform well in their sports, and many athletes have turned to vision training programs as a way to augment their traditional training regimen. The growing practice of 'sports vision training' relies on the notion that practice with demanding visual perceptual, cognitive, or oculomotor tasks can improve the ability to process and respond to what is seen, thereby improving sport performance. This enterprise is not necessarily new, but has been advanced greatly in the past few years by new digital technology that can be deployed during natural training activities, by perceptual-learning-inspired training programs, and by virtual reality simulations that can recreate and augment sporting contexts to promote certain sports-specific visual and cognitive abilities. These improved abilities may, in turn, instill a competitive advantage on the playing field, underscoring the potential value of these approaches. This article reviews emerging approaches, technologies and trends in sports vision training. Where available, critical review of supporting research is provided.